2003
DOI: 10.1007/s00427-003-0334-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biological functions of a doublesex homologue in Bombyx mori

Abstract: We have previously reported that Bmdsx, a homologue of the sex-determining gene doublesex ( dsx), was sex-specifically expressed in various tissues of the silkworm. The primary transcript of Bmdsx is alternatively spliced in males and females to yield sex-specific mRNAs that encode male-specific (BmDSXM) and female-specific (BmDSXF) polypeptides. In the studies reported here, we expressed BmDSXF in males from a ubiquitous promoter and examined its regulatory activities. We show that BmDSXF functions as a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
111
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 37 publications
3
111
0
5
Order By: Relevance
“…In addition, recent studies suggest that changes in temporal and spatial expression of dsx by gene regulatory networks providing positional information may contribute to this diversity [Rideout et al, 2010;Robinett et al, 2010]. A prominent role of dsx in properly implementing the selected sexual developmental program has not only been validated in D. melanogaster [Baker and Wolfner, 1988], but also in other dipterans, M. domestica [Hediger et al, 2004] and C. capitata [Saccone et al, 2008], in the lepidopteran B. mori [Suzuki et al, 2003[Suzuki et al, , 2005 as well as in the coleopterans T. castaneum [Shukla and Palli, 2012a] and horned beetles [Kijimoto et al, 2012]. Hence, dsx is thought to play a widely conserved role in integrating information about sexual identity in the general developmental program [Vincent et al, 2001].…”
Section: Downstream Events In Sexually Dimorphic Developmentmentioning
confidence: 99%
“…In addition, recent studies suggest that changes in temporal and spatial expression of dsx by gene regulatory networks providing positional information may contribute to this diversity [Rideout et al, 2010;Robinett et al, 2010]. A prominent role of dsx in properly implementing the selected sexual developmental program has not only been validated in D. melanogaster [Baker and Wolfner, 1988], but also in other dipterans, M. domestica [Hediger et al, 2004] and C. capitata [Saccone et al, 2008], in the lepidopteran B. mori [Suzuki et al, 2003[Suzuki et al, , 2005 as well as in the coleopterans T. castaneum [Shukla and Palli, 2012a] and horned beetles [Kijimoto et al, 2012]. Hence, dsx is thought to play a widely conserved role in integrating information about sexual identity in the general developmental program [Vincent et al, 2001].…”
Section: Downstream Events In Sexually Dimorphic Developmentmentioning
confidence: 99%
“…Like dsx, the primary transcript of the Bmdsx gene is alternatively spliced in males and females to yield sex-specific mRNAs that encode male-specific (BmDSXM) and female-specific (BmDSXF) polypeptides (34,42). Transgenic analysis of Bmdsx revealed that Bmdsx functions as a double-switch gene at the bottom of the sex determination cascade of B. mori (43,44). Despite these similarities between dipteran dsx orthologues and Bmdsx, the underlying mechanisms for sex-specific splicing are clearly different.…”
mentioning
confidence: 99%
“…Like dsx, the primary transcript of the Bmdsx gene is alternatively spliced in males and females to yield sex-specific mRNAs that encode male-specific (BmDSXM) and femalespecific (BmDSXF) polypeptides (36,42). Transgenic analysis of Bmdsx revealed that Bmdsx functions as a double-switch gene at the final step in the B. mori sex determination cascade (43,44). Despite these similarities between dsx and Bmdsx, the underlying mechanism for sex-specific splicing is clearly different.…”
mentioning
confidence: 99%